2018
DOI: 10.3389/fmed.2018.00146
|View full text |Cite
|
Sign up to set email alerts
|

Phage Therapy: Beyond Antibacterial Action

Abstract: Until recently, phages were considered as mere “bacteria eaters” with potential for use in combating antimicrobial resistance. The real value of phage therapy assessed according to the standards of evidence-based medicine awaits confirmation by clinical trials. However, the progress in research on phage biology has shed more light on the significance of phages. Accumulating data indicate that phages may also interact with eukaryotic cells. How such interactions could be translated into advances in medicine (es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 94 publications
0
21
0
7
Order By: Relevance
“…Moreover, phages -being considered the most common biological entities on earth (Papaianni et al, 2018) -can be found in a variety of forms and environments (Koskella and Meaden, 2013). They are non-toxic for eukaryotic cells, and, due to their specificity, may not harm the soil beneficial microbiota (Capparelli et al, 2010;Reddy, 2013;Górski et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, phages -being considered the most common biological entities on earth (Papaianni et al, 2018) -can be found in a variety of forms and environments (Koskella and Meaden, 2013). They are non-toxic for eukaryotic cells, and, due to their specificity, may not harm the soil beneficial microbiota (Capparelli et al, 2010;Reddy, 2013;Górski et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Despite being able to interact with phagocytic cells and be adsorbed through mammalian cells' surface receptors, being subsequently phagocytosed and degraded, they are not threatening. 10,12,17 Several studies have explored the potential of systemic phages administration for the treatment of implant-related infections. [13][14][15][18][19][20][21] Nonetheless, experimental studies using phages-loaded biomaterials for local delivery approaches are scarce, 9,22,23 focusing on the phages release and antimicrobial activity, without simultaneously exploring the potential combination with a regeneration inductive biomaterial.…”
mentioning
confidence: 99%
“…While the most trustworthy advances come through the performance of well-designed trials, sometimes experimental treatments based on theoretical considerations alone may lead to major breakthroughs [ 284 ]. As stated, “the potential for broader application of phage therapy is evident and it is certainly worthy of further studies” [ 285 ].…”
Section: Pt: Beyond the Antibacterial Actionmentioning
confidence: 99%